TABOO IN WULLA PODDU “BULAN PEMALI” IN LOLI COMMUNITIES WITH MARAPU BELIEFS OF WEST SUMBA REGENCY AND ITS EDUCATIONAL VALUES - DJAWA, ALEX; DJULI, LABU; SAMPE, MARKUS (Postgraduate School, Universitas Nusa Cendana, 2022)
The Loli people who adhere to the Marapu belief are people who are very obedient to the teachings and values ​​that they adhere to. Various forms of taboos were found, including: the taboo of the dead, the taboo on intercourse by Rumata (High Priest), cutting down large trees, slaughtering large animals, not two people may carry wood, more than one person may not carry wood, and may not crush wood. paddy, defending wood and shouting at night, may not build traditional houses, may not hold parties, may not marry women, and music may not be sounded loudly. Taboo has educational values ​​regarding relations with God and humans. Values ​​teach obedience and fear of God. With taboos, people become obedient and fearful because of curses, illnesses, suffering, and woes.